2023
DOI: 10.3390/biomedicines11092480
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perspectives of Gut Microbiota in Patients with Chronic Kidney Disease and End-Stage Kidney Disease: Where Do We Stand?

Alexandru Cosmin Pantazi,
Mustafa Ali Kassim Kassim,
Wassan Nori
et al.

Abstract: The gut microbiota (GM) plays a vital role in human health, with increasing evidence linking its imbalance to chronic kidney disease and end-stage kidney disease. Although the exact methods underlying kidney-GM crosstalk are not fully understood, interventions targeting GM were made and lay in three aspects: diagnostic, predictive, and therapeutic interventions. While these interventions show promising results in reducing uremic toxins and inflammation, challenges remain in the form of patient-specific GM vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 171 publications
0
5
0
Order By: Relevance
“…Thus, we found disturbances of the microbial flora in various atopies (asthma, dermatitis, food allergies), autoimmunity (systemic lupus erythematosus, CD, diabetes, autoimmune thyroiditis), organic insufficiency (cardiac, renal), neurological, oncological or metabolic disorders. To these are added inflammatory conditions (e.g., pancreatitis), respiratory infections, irritable bowel, gastroenteritis, esophagitis, gastroesophageal reflux disease or diverticular disease, pathologies frequently encountered in medical practice (30)(31)(32)(33)(34)(35)(36). The oral and intestinal microbiota of patients with CD is strongly influenced by a variety of factors, starting from the impact of genetic determinants, the environment (antibiotics, infections) and even the gluten-free diet.…”
Section: Pathogenesismentioning
confidence: 99%
“…Thus, we found disturbances of the microbial flora in various atopies (asthma, dermatitis, food allergies), autoimmunity (systemic lupus erythematosus, CD, diabetes, autoimmune thyroiditis), organic insufficiency (cardiac, renal), neurological, oncological or metabolic disorders. To these are added inflammatory conditions (e.g., pancreatitis), respiratory infections, irritable bowel, gastroenteritis, esophagitis, gastroesophageal reflux disease or diverticular disease, pathologies frequently encountered in medical practice (30)(31)(32)(33)(34)(35)(36). The oral and intestinal microbiota of patients with CD is strongly influenced by a variety of factors, starting from the impact of genetic determinants, the environment (antibiotics, infections) and even the gluten-free diet.…”
Section: Pathogenesismentioning
confidence: 99%
“…The gut-kidney axis is a burgeoning area of research. Dietary interventions that modulate gut microbiota, such as prebiotics and probiotics, may offer new therapeutic avenues for CKD management (Pantazi et al, 2023) [14] . 3.…”
Section: Role Of Gut Microbiotamentioning
confidence: 99%
“…The activation of immune cells, leading to a low-grade inflammatory reaction, affects the kidneys. Moreover, the peripheral nervous system alters neural inputs to the kidney, thus promoting further kidney dysfunction [78]. Additionally, it has been suggested that there is a specific intestinal flora that has a causal relationship with the incidence and progression of chronic kidney disease at the level of gene prediction [79].…”
Section: Diureticsmentioning
confidence: 99%